ANALISIS POTENSI EKSPOR CPO (CRUDE PALM OIL) DI SUMATERA UTARA - Anastasya Elanmoy Siahaan; Murni Daulay (Departemen Ekonomi Pembangunan USU, 2013)
This study aims to determine how the exchange rate, production, international price of CPO, and economic growth in North Sumatra affect CPO export to the world market. The variables studied were the exchange rate, production, international price of CPO and CPO exports and economic growth. And also to look at trends and projections CPO North Sumatra. The data used are secondary data. The method used is the method of regression analysis to look at the factors that affect CPO eksor North Sumatra and using the Trend and projections to see trends and projections CPO exports from year 2012 to 2020. The results showed a negative exchange rate effect on exports and significant CPO North Sumatra. While the variable price of CPO and International Economic Growth positive effect on CPO exports of North Sumatra and significant. Production variables and positive effect on CPO exports of North Sumatra and not significant. Simultaneously, all the variables are Exchange Rates, Production, International price of CPO and Economic Growth positive and significant impact on CPO exports. And based on Trend and projections Ekpsor CPO North Sumatra visible trend has increased and projections are also increasing from year 2012 to 2020.Keywords: Price International CPO, Production, Exchange Rate, Economic Growth, Trends and Projections CPO exports.